The air transportation industry : economic conflict and competition - Macario, Rosario; Voorde, E. van de (Eddy) (Contemporary issues in air transport., 2022)
The aviation sector consists of various actors such as airlines, ground handling companies, and others all with conflicting priorities. In order to understand how these actors position themselves in an increasingly competitive market, The Air Transportation Industry: Economic Conflict and Competition analyzes all the market segments in detail, examining such issues as which industrial economic structure drives decisions, the main economic problems, the consequences for negotiations between different actors, impacts on the global aviation market, and much more. This book covers the entire aviation sector including strategies, regulation, resilience, privatization, airport slot management, and more. It examines how economic and strategic struggles underlie the current market structure, both for aviation as a whole and for the constituent actors as carriers, authorities, and handlers. It examines the ways market and nonmarket approaches impact the competitiveness of the air transport industry, offering a complete mapping of the economic actions between actors of the air transport industry. This volume will help readers gain insight into the possible strategic choices and the mutual competitive strength within the future aviation market.